Bacterial Lysates as Immunotherapies for Respiratory Infections: Methods of Preparation - Suárez, Norma; Ferrara, Florencia; Rial, Analia; Dee, Valerie; Chabalgoity, Jose A. (Frontiers in Bioengineering and Biotechnology, 2020)
Bacterial lysates, prepared from the microorganisms most frequently involved in human Respiratory Tract Infections (RTIs) have been in the market for several decades, and at present, several different brands are available in many countries worldwide. They all claimed to exert local and systemic immunomodulatory effects but different clinical trials show disparate results between them. The lack of consistency of predicted therapeutic effects has undermined their clinical use and hampered licensing in several countries. One explanation for such a lack of consistency in the results is that their methods of preparation are also very different. Here, we review the available literature describing methods of preparation of bacterial lysates, including patent disclosure documents. We found a great variety of methodologies of preparation and a lack of standardized procedures among them. The main conclusion of our study is that there is a clear need for standardized protocols of production to obtain comparable results in clinical trials worldwide.